(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Computational linguistics, or natural language processing (NLP - Natural Language Processing), is a modern branch of science that studies the interaction between human language and computers. This field is aimed at understanding, analyzing and re-engineering the complexities of human language with the help of computers, and today it has become an integral part of technological development.